Mesoporous silica-based versatile theranostic nanoplatform constructed by layer-by-layer assembly for excellent photodynamic/chemo therapy. (February 2017) - Chen, Wei-Hai; Luo, Guo-Feng; Qiu, Wen-Xiu; Lei, Qi; Liu, Li-Han; Wang, Shi-Bo; Zhang, Xian-Zheng
Abstract: Supramolecular photosensitizers (supraPSs) have emerged as effective photodynamic therapy (PDT) agents. Here, we propose the assembling capacity of supraPSs as a new strategy to construct theranostic nanoplatform with versatile functions aming at high-performance tumor therapy. By coating tirapazamine (TPZ)-loaded mesoporous silica nanoparticles (MSNs) with layer-by-layer (LbL) assembled multilayer, the versatile nanoplatform (TPZ@MCMSN-Gd 3+ ) was obtained with the formation of supraPSs via host-guest interaction and the chelation with paramagnetic Gd 3+ . The TPZ@MCMSN-Gd 3+ could be specifically uptaken by CD44 receptor overexpressed tumor cells and respond to hyaluronidase (HAase) to trigger the release of therapeutics. As confirmed by in vivo studies, TPZ@MCMSN-Gd 3+ showed preferential accumulation in tumor site and significantly inhibited the tumor progression by the collaboration of PDT and bioreductive chemotherapy under NIR fluorescence/MR imaging guidance. Taken together, this supraPSs based strategy paves a new paradigm of the way for the construction of theranostic nanoplatform.